(untitled) (SAARC Journal of Agriculture, 2024)
Local Thrabam cattle were inseminated with semen of four sire-lines of Tropical Holstein Friesian (THF) at selected sites of three agro-ecological zones of Bhutan. To understand their performances, progeny born from each sire-line were recorded and milk yield of F1 daughters were measured. Management practices were observed through farm visits. Result indicated that insemination in natural heat produced significantly higher calves than in induced heat (p<0.005). Average daily milk yield of F1 daughters was 5.2±2.5 l/day. Some farmers mated F1 daughters at about one year of age, before animal reached the desired body weight. This disturbed growth of dam and few such dams faced calving difficulties. Cattle were managed through open grazing during the day (81%) and sheltered at night. Only 25% of farms provided supplementary feed to milking animals/calves. Minimal calf mortality (2.93%) with no reported adult mortality indicated the crossbreds adapt well to the local environment. The present study concluded that for more calf-crops, insemination in natural heat should be advocated and mating of F1 daughter at tender age needs to be discouraged. Under prevailing management system, F1 daughters were performing optimally. However, with the increase in THF inheritance level, cattle management needs to be improved to maximize output. SAARC J. Agric., 22(1): 235-242 (2024)